DRAFT MAPUTO STATEMENT ON HIV AND AIDS IN SOUTHERN AFRICA - Conference Delegates (PINS-Psychology in Society, 2025)
This statement was prepared and agreed to by delegates at an International Conference on Health in Southern Africa held in Maputo, Mozambique in April 1990. This important event brought together a wide range of progressive organisations inside and outside South Africa, including the African National Congress, the United Democratic Front, and health and welfare workers from a wide variety of organisations. The conference benefited from the contributions of activists and grassroots members of community, political and progressive health organisations. In addition, people working in the Frontline States elsewhere in Africa, the United Kingdom and United States contributed valuable insights and experiences.